2015
DOI: 10.1111/faf.12120
|View full text |Cite
|
Sign up to set email alerts
|

Marine ornamental fish imports in the European Union: an economic perspective

Abstract: The marine ornamental fish trade (MOFT) is a worldwide industry that targets a remarkable quantity and diversity of reef fish species and provides an important source of revenue for exporting countries, particularly developing nations in Southeast Asia. Here we provide, for the first time, an economic assessment of the MOFT to the European Union (EU), one of the key players of the marine aquarium trade, along with the USA and Japan. Data from EUROSTAT (the European Statistical System) was analysed for the MOFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…4) and distributing them to all EU member states, as well as other non-member states (e.g., Switzerland, Norway and Russia). None of the suppliers was previously informed about the survey being performed, in order to avoid any shift in their modus operandi .…”
Section: Methodsmentioning
confidence: 99%
“…4) and distributing them to all EU member states, as well as other non-member states (e.g., Switzerland, Norway and Russia). None of the suppliers was previously informed about the survey being performed, in order to avoid any shift in their modus operandi .…”
Section: Methodsmentioning
confidence: 99%
“…implementation of eco-fees to support research on marine ornamental fisheries and mariculture (Leal et al 2015)). …”
Section: Holocentrus Adscensionismentioning
confidence: 99%
“…fish, corals and a wide variety of invertebrate species) to supply aquaria kept by 2 million hobbyists worldwide (Wabnitz et al 2003, Rhyne et al 2012a. It is estimated that the activity targets over 1,800 reef fish species from 125 families, over 150 species of stony corals and hundreds of species of non-coral invertebrates (Rhyne et al 2012b, Rhyne et al 2014, Leal et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Tracing the geographical origin and source (wild caught v . captive‐bred) of traded specimens is a challenging task that is commonly doomed to failure due to long, fragmented and highly complex supply chains (Leal et al, ). In the present study we have only been able to ascribe the fishes observed to broad geographic origins based on their known distributions in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…Using what has come to be known as the global marine aquarium database (GMAD), the authors revealed a total of 1471 species of fish are traded worldwide (Wabnitz et al, ) although a study by Rhyne et al () estimated this figure to be nearer to 1800 in the US alone. Leal et al () provided the first economic assessment of the ornamental reef‐fish trade in Europe revealing a total value of > €135 million over an 11 year period. The UK was identified as the largest importing country and its dominance as a trade centre among other EU countries was found to have increased in recent years rising from 14% of total imports in 2000 to 26% in 2011.…”
Section: Introductionmentioning
confidence: 99%